Transition of dome formation to sudden explosive eruptions at Popocatépetl, Mexico: magnetic indicators - Martin-Del-Pozzo, Ana Lillian; Santos Morales, César Alberto (Frontiers in Earth Science, 2024)
Transitions from effusive to explosive activity can increase hazards making it crucial to define early indicators such as changes in the magnetic signals. After more than 80 cycles of crater-dome extrusion and destruction from 1996 on, Popocatépetl volcano (Mexico) experienced changes in its behavior from March 15 to 18 July 2019, when no lava domes were observed. Some of the domes behaved as contained lava flows within the crater floor (pancakes) while others were more irregular-shaped. Activity decreased considerably over this 2019 interval except for the unexpected explosions in March and June, that produced ash plumes reaching up to 14,000 m a.s.l. In order to investigate the causes of the transition from effusive to explosive behavior in March and June, we analyzed the time series from the magnetic monitoring network at Popocatépetl volcano between October 2018 and December 2019. The raw signals were analyzed by weighted differences (WD) based on the elimination of non-local changes from the total intensity values of the geomagnetic field and the discrete-time continuous wavelet transform was used to evaluate the local variations of energy within the time series. The high energy periods (linked to negative magnetic anomalies) are induced by magma ascent associated with movement within the conduit. They indicate that the sudden explosions were due to the ascent of several magma batches that were slowed during ascent and were not able to reach the surface. Changes in the rheology of the lava are linked to the influx of several batches of magma with different compositions as well as to compaction by gas loss when ascending andesitic magma pushed out overlying more viscous degassed magma clearing the conduit, which can explain why these sudden explosions were more energetic. Several geophysical data sets as well as tephra compositions were integrated to support this conclusion. The correlated multiparameters also confirm that geomagnetic volcano monitoring has been essential in understanding the processes that drive the observed changes in eruptive behavior. We present new evidence for the detection of transient events produced by magma ascent and changes in the feeding system of Popocatépetl volcano with wavelet analysis. Detailed vulcanomagnetic processing, especially when it is correlated with other monitoring parameters, provides information on ascending magma and several conduit processes that would otherwise be camouflaged. Ascending batches may precede an eruption but they can also ascend in several pulses indicating how dome growth occurs.